2022
DOI: 10.1063/5.0090811
|View full text |Cite
|
Sign up to set email alerts
|

Correlation lengths in nanoconfined water and transport properties

Abstract: We report the existence of disparate static and dynamic correlation lengths that could describe the influence of confinement on nanoconfined water (NCW). Various aspects of viscous properties, such as anisotropy, viscoelasticity among others, of NCW are studied by computer simulations by varying the separation 'd' between the two confining hydrophobic plates. The mean square stress exhibits a slow spatial decay (measured from the surface) beyond ~1.8 nm. The static correlation length obtained from fitting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…This model also assumes that hydrodynamics applies in such highly confined systems. Previous studies already showed the applicability of the hydrodynamics in similar confined systems. ,,,, Finally, the CSE relation (eq ) assumes that the hydrodynamic diameter of bulk water is the same as the water inside CNTs. In other words, the extent of breakdown of the SE relation in bulk water is the same as the confined water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model also assumes that hydrodynamics applies in such highly confined systems. Previous studies already showed the applicability of the hydrodynamics in similar confined systems. ,,,, Finally, the CSE relation (eq ) assumes that the hydrodynamic diameter of bulk water is the same as the water inside CNTs. In other words, the extent of breakdown of the SE relation in bulk water is the same as the confined water.…”
Section: Methodsmentioning
confidence: 99%
“…However, this is not always true. Some of the circumstances when the SE relation is not completely obeyed include water in confinement, , water in a supercooled state, ,, water under high pressure, and the presence of another solvent. Therefore, some modification(s) of the existing CSE approach are necessary for a more robust estimation of viscosity of water in different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In the expression for shear viscosity (eq ), the stress tensor σ αβ consists of five independent components: σ xy , σ yz , σ zx , 1 2 ( σ italicxx σ italicyy ) , and 1 2 ( σ italicyy σ italiczz ) . For isotropic systems, all of these five components are equivalent. , …”
Section: Concentration-dependent Shear Viscositymentioning
confidence: 99%
“…For isotropic systems, all of these five components are equivalent. 64,67 First, we calculated the shear viscosity of the SPC/E and the TIP4P/2005 water models and obtained values of 0.73 and 0.86 mPa s, respectively. The results are in good agreement with the previous studies.…”
Section: Concentration-dependent Shear Viscositymentioning
confidence: 99%
“…In recent years, there has been increasing interest in the study of confined systems and their applications in several fields owing to modifications in their chemical and physical properties. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Some examples of these applications are the use of molecular cages as nanocontainers, 15 the design of materials with specific optical properties, [16][17][18][19][20] the development of rechargeable ion batteries, 21 the fabrication of gas sensors to detect pollutant gases, 22 the study of quantum-chemical models of enzyme active sites, 23 the use of nanocarriers as drug delivery systems for tumor treatments, 24 the improvement of nanoelectronic devices, 25 and the understanding of certain modifications in the properties of atoms and ions in a plasma environment. 26,27 In particular, the storage and transport of hydrogen has attracted a great deal of attention due to its use as a clean source of energy, 28,29 and several theoretical and experimental works have focused on this subject under different confining situations.…”
Section: Introductionmentioning
confidence: 99%